(untitled) (Historia, 2021)
Luli Callinicos has earned a well-deserved reputation for excellence in the field of popular history with the first two volumes in the series A people’s history of South Africa. The quality of both Gold and workers 1886-1924 (1980) and Working life 1886-1940 : Factories, townships, and popular culture on the Rand (1987) has been widely recognised by professional historians, teachers of history and their students, as well as members of the wider public interested in South Africa’s past; in addition, the latter publication won the prestigious Noma Award for Publishing in Africa.